FAKTOR-FAKTOR YANG MEMPENGARUHI CURAHAN KERJA PETANI ORANG ASLI PAPUA (OAP) DI KAMPUNG BOGOR DISTRIK PRAFI KABUPATEN MANOKWARI - Sarira, Gebrilla Salissing; Tjolli, Ihwan; Puspita Sari, Ardha (Sosio Agri Papua, 2024)
This research was conducted in Bogor Village, Prafi District, Manokwari Regency, this research aims to determine the factors that influence the outpouring of farming work in Bogor Village, Prafi District, Manokwari Regency. Determination of the sample using a simple random method. The number of samples used in this research was 30 people. The data used in this research is primary data supported by secondary data obtained from related agencies. To determine the influence of age, formal education, number of family members, land area and income from outside farming on the volume of agricultural work in Bogor Village, Prafi District, Manokwari Regency, using multiple linear regression analysis tools. Based on the results of multiple linear regression analysis. Based on the results of data processing via SPSS, it is known that the coefficient of determination R Square is 0.570, which means that 57% of the rise and fall of work volume (Y) is influenced by age (X1), formal education (X2), number of family members (X3), land area ( X4) and non-farming revenues (X5) and the remaining 43% is influenced by other factors outside the model. From the results of the F test which was significant (α=0.05), a probability value of 0.001 was obtained so that it was concluded that the variables age, formal education, number of family members, land area and income from outside the farm simultaneously influenced the outpouring of farming work, but partially the number of members family and land area have a significant influence. Key words: Work rate, age, formal education, number of family members, outside land and income from outside farming